VILLAGE POTENTIAL THROUGH MSMES IN MANGUNREJO VILLAGE, NGADILUWIH DISTRICT, KEDIRI DISTRICT - Rahmadi, Afif Nur; Imam Mukhlis; Yudiarto Perdana Putra (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
A village is a legal community unit that has the authority to regulate and manage government affairs, the interests of the local community based on community initiatives, origin rights, and/or traditional rights that are recognized and respected in the government system of the Unitary State of the Republic of Indonesia. The subjects of this research were the community, community leaders and government officials in Mangunrejo Village, Ngadiluwih District, Kediri Regency. The conclusion that can be drawn from the research above is that SMEs in Mangunrejo Village need assistance with a total of 79 SMEs and there is a lack of product development and distribution training for SMEs in Mangunrejo Village, Kediri Regency.